2000
DOI: 10.2527/jas2000.77e-suppl1q
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine regulation of reproduction in male domestic animal species: Role of excitatory amino acids

Abstract: The ability to control and enhance reproduction in male domestic animal species requires a sound understanding of the mechanisms functioning within the hypothalamic-pituitary-testicular axis. Recent evidence suggests that the excitatory amino acids (ExAA) are important neurotransmitters that participate in the neuroendocrine control of anterior pituitary hormone secretion. In general, treatment with agonists of different ExAA receptor types, such as n-methyl-D,L-aspartate (NMA), stimulate release of most anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Effects of NMA with i.v. injection on animal endocrine system, particularly in reproductive hormones, have been well documented (Estienne et al, 1997(Estienne et al, , 1999. Only few papers reported the effects of NMA on animals with oral administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of NMA with i.v. injection on animal endocrine system, particularly in reproductive hormones, have been well documented (Estienne et al, 1997(Estienne et al, , 1999. Only few papers reported the effects of NMA on animals with oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Excitatory amino acids (EAA), such as glutamate and asparate, are major neurotransmitter in the mammalian central neurons system, which generally stimulate (primary via N-methyl-d-aspartate, NMDA receptor) the release of neuropeptides from the central nervous system, thereby influencing pituitary functions. Abundant studies have indicated that n-methyl-d,l-aspartate (NMA), an agonist of glutamate, increases pituitary secretion of LH and GH under appropriate conditions in a variety of domestic animal species (Estienne et al, 1996a(Estienne et al, , 1997. For example, NMA at an i.v.…”
Section: Introductionmentioning
confidence: 99%